Total Suspended Solid (TSS) Distributed by Tidal Currents during Low to High Tide Phase in the Waters of Sayung, Demak: Its Relations to Water Quality Parameters - Wisha, Ulung Jantama; Ondara, Koko (Journal of Marine and Aquatic Sciences; Vol 3 No 2 (2017), 2017)
Sayung waters is a region highly vulnerable to catastrophic erosion along the coast, which is directly followed by an increase suspended sediments and particles from the bottom of the waters that was stirred by oceanography factors. The purpose of this study was to determine the concentration and distribution of the latest TSS condition and its effect on water quality parameters in the waters of Sayung. The sampling method is using purposive sampling, with the stations spread out along the coastal area of Sayung, the main data consist of current, tide, bathymetry, coastline and water quality, and the secondary data consist of RBI map and tide forecasting, those data is analyzed numerically and statistically. TSS value ranged between 23,1-199,6 mg.L -1 , the distribution of TSS is simulated in the condition of ebb to tide with current speed ranged between 0-0.41 ms -1 , that distribution also influenced by physical water factors such as salinity, temperature, and density and has  impacts to enhancing the turbidity and indirectly decrease the photosynthesis activity and inhibit the oxygen cycle in the Sayung waters.
Keywords: hydrodynamics; Sayung waters; total suspended solid; water quality